Asymmetric Information, Financing Constraints, and Investment - Fazzari, Steven M.; Athey, Michael J. (The Review of Economics and Statistics, 1987)
The results of a number of theoretical papers lead to the hypothesis that financial variables affect capital sp ending because of asymmetric information in capital markets. The auth ors review the relevant theory and test this hypothesis with a large sample of firm data. The results show that financial variables such a s cash flow and interest expense add significant explanatory power to investment equations based on Dale Jorgenson's neoclassical model, w ith a CAPM specification for the firm's cost of capital, and a sales- accelerator model. The analysis, therefore, links recent theoretical work on capital markets to long-standing empirical debates in the inv estment literature. Copyright 1987 by MIT Press.